PERAN KEPUASAN KERJA MEMEDIASI PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Halman, Ariatmi; Ridjal, Syamsul; Djaharuddin, Dharmawaty (AkMen JURNAL ILMIAH, 2023)
This research aims to determine and analyze the influence of motivation and organizational culture on employee performance mediated by job satisfaction. This type of research is descriptive research with a quantitative approach. The sample in this study was 58 sub-district employees in Binamu District, Jeneponto Regency using a sample collection method using saturated samples. The data analysis method used is descriptive statistical analysis and path analysis. The research results show that motivation has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, and job satisfaction has a significant positive effect on employee performance. Motivation has a positive and significant effect on employee performance through job satisfaction. Culture has a positive and insignificant effect on performance through job satisfaction of sub-district employees in Binamu District, Jeneponto Regency.